The Curriculum of Love as a Humanistic Solution in Addressing Juvenile Delinquency - Nurhikmah, Novisya; Irnawati, Putri; Aulia, Nazwa; Hindun, Hindun (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research aims to analyse forms of juvenile delinquency in Indonesia through the perspective of humanistic theory, and to examine the relevance of the Love-Based Curriculum as a preventive and curative solution to juvenile delinquency. Through a qualitative-descriptive approach, data was collected through case analysis of digital newspapers, then analysed by comparing adolescent behavioural patterns against humanistic theories from experts. The research findings indicate that juvenile delinquency stems from unmet needs for affection, social acceptance, and self-esteem. A curriculum based on love is seen as capable of being a preventive strategy by instilling values of affection and acceptance in the education sector, and as a curative solution through empathetic guidance that can restore adolescents’ sense of self-worth. The implications of this research require a reformulation of the direction of national education towards a humanistic approach to create a generation of young people who are characterised by love and social responsibility.